ORCHAMP: an observation network for monitoring biodiversity and ecosystem functioning across space and time in mountainous regions - Thuiller, Wilfried; Saillard, Amélie; Abdulhak, Sylvain; Augé, Vincent; Birck, Carole; Bonet, Richard; Choler, Philippe; Delestrade, Anne; Kunstler, Georges; Leccia, Marie-France; Lienard, Bertrand; Poulenard, Jérome; et al. (Comptes Rendus Biologies)
Recent climate and land use change, and pollution have led to concerning alterations in biodiversity and ecosystem functions, jeopardizing nature’s contributions to people. Mountainous regions are not immune to these threats, experiencing the impacts of global warming, increased recreational activities, and changes in agricultural practices. Leveraging the natural elevational gradients of mountain environments, the ORCHAMP program was established in 2016 as a comprehensive initiative to monitor, understand, and predict the repercussions of environmental changes on biodiversity and associated ecosystem functions in the French Alps and Pyrenees.Beyond its monitoring role, ORCHAMP has catalyzed the development of tools for data integration, statistical analyses, visualization, and AI-based automated data processing and predictions. Through a combination of traditional sampling methods (e.g., botanical surveys) and cutting-edge technologies (remote-sensing, environmental DNA, video, and acoustic sensors), the program offers a holistic approach to understanding how biodiversity faces environmental changes. By showcasing examples and key results, this paper provides an overview of ORCHAMP’s advancements and outlines potential future directions. The broad inclusion of diverse monitoring techniques and data treatments positions ORCHAMP as a pioneering effort, paving the way for long-term insights into biodiversity dynamics—a crucial step toward effective conservation strategies.